RELATIONSHIP BETWEEN GEOGRAPHY AND LAW: BIBLIOGRAPHICAL NOTES - Souza, Jonas Dias (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2013)
This article makes notes about the relationship between Geography and Law based on a literature review of the subject and indicate authors that currently discussing the issue. Initially, we present the Geography and Law relationship history and, next, we describe four theoretical and methodological proposals for the development of Geography of Law. Finally, we discuss some issues that have been most frequently studied by the authors, trying to find a common denominator between them. In general, although there is no theoretical common ground the studies show a very geographical dimension on Law which depends its operability and legitimacy.